Production of Pectic Oligosaccharides from Citrus Peel via Steam Explosion - Toni-Ann Martorano; Kyle L. Ferguson; Randall G. Cameron; Wei Zhao; Arland T. Hotchkiss; Hoa K. Chau; Christina Dorado (Foods)
Steam explosion (STEX) of peel from commercially juice-extracted oranges was used to convert peel pectin into pectic oligosaccharides (POSs). Surprisingly uniform populations, based on the polydispersity index (PDI; weight-average molecular weight (Mw)/number-average molecular weight (Mn)) of POSs, were obtained from the Hamlin and Valencia varieties of Citrus sinensis. The POSs from Hamlin and Valencia peel had PDI values of (1.23 ± 0.01, 1.24 ± 0.1), respectively. The Mw values for these samples were 14.9 ± 0.2 kDa for Hamlin, and 14.5 ± 0.1 kDa for Valencia, respectively. The degree of methyl-esterification (DM) was 69.64 ± 3.18 for Hamlin and 65.51 ± 1.61 for Valencia. The composition of the recovered POSs was dominated by galacturonic acid, ranging from 89.1% to 99.6% of the major pectic sugars. Only the Hamlin sample had a meaningful amount of rhamnose present, indicating the presence of an RG I domain. Even so, the Hamlin sample’s degree of branching (DBr) was very low (2.95).